Analisis Semiotika Pesan Moral Film Ku Kira Kau Rumah - BERLIANA, MAHDALENA; Abidin, Sholihul (SCIENTIA JOURNAL, 2023)
The existence of films in the midst of society has a different character compared to other media Apart from being an effective mass media in conveying ideas and ideas, film is also a medium to express an art to express a creativity and to describe human life. The film Ku Kira Kau Rumah tells the story of a girl named Niskala who suffers from bipolar disorder, a mental health issue that can relapse and attack her at any time. The purpose of this study is to find out the moral message represented by the film Ku Kira Kau Rumah. The research method used is a qualitative research method. Qualitative research is research whose data is in the form of statements or statements and begins with an interpretive approach. By using the semiotic approach of Roland Barthes perspective through denotation, connotation and myth. The results showed that Niskala's bipolar disorder was a mental health disorder, and she often experienced mood swings or very rapid mood changes. The moral message contained in the film "Ku Kira Kau Rumah" consists of relationships between family, friends, and partners, which include attention, full of hope, full of affection, honesty, perseverance, wisdom, openness, trust in others, and humility. Conclusion Moral values in Ku kira Kau Rumah can provide a teaching about family, friendship, courage in pursuing dreams and appreciating every opportunity, trust and sincerity so that the audience can face life with optimism, and appreciate an important relationship in life and not give up easily. Keywords: Film, Moral Message, Semiotics Perspective Ferdinand De Saussure